Powering the Future under Geopolitical Pressure-PV Industry Analysis for China and USA - Zhang, Zijian (Transactions on Economics, Business and Management Research, 2024)
This paper examines the current state of the photovoltaic (PV) industry, which is a significant contributor to global environmental protection efforts. The PV industry’s status is closely linked to environmental sustainability, one of the most pressing issues of our time. This study evaluates the current situation of PV panels, assesses potential risks to the industry’s stability, and proposes solutions to mitigate these threats. The analysis focuses on China and the USA due to their significant roles in the global PV market and their anticipated future influence. By examining the economic perspectives and geopolitical factors affecting the PV industry in these two countries, this paper aims to provide a comprehensive understanding of the current dynamics and future outlook. Government policies, including supply-side measures like tax incentives and demand-side initiatives such as feed-in tariffs, heavily influence China’s PV industry. Recent trends indicate a shift towards marketization and refinement. In contrast, the US PV industry is driven more by market-based demand-side policies and is significantly impacted by economic factors and geopolitical considerations, including trade protectionism aimed at safeguarding its new energy sector. Through this comparative analysis, the paper seeks to identify the strengths and weaknesses of each country’s approach, offering insights into how the global PV industry can navigate its challenges and continue to contribute to environmental sustainability.